Mapping of Healthy Homes in Koto Tibun Village - Febrian, Irfan; Setiawan, Beny (Journal of Engineering Science and Technology Management (JES-TM), 2022)
Healthy house is a building for shelter and rest and as a means of fostering a family that fosters a healthy life physically, mentally and socially, so that all family members can work productively. Koto Tibun Village is one of the villages in Kampar Regency located in Kampar District. The lack of public knowledge about healthy houses in Koto Tibun Village is relatively low, because most people build houses with their own business or only use the services of local handymen without proper planning. In Koto Tibun Village, there are still some houses that do not meet the requirements for healthy houses due to lack of lighting, ventilation size, healthy latrines, garbage disposal, dirty water disposal, floors and also ceilings/asbestos. In this regard, it is necessary to conduct a survey of healthy houses in Koto Tibun Village, Kampar District so that the proportion of existing healthy houses can be known and a targeted plan can be prepared. Based on this explanation, the author is interested in researching more about the distribution of healthy houses in Koto Tibun Village. The data collection techniques used in this study were field observation, interview and questionnaire. The results obtained from this study showed that there were 25 or 27.47% of the study subjects who were residential houses that belonged to the category of healthy houses and the remaining 66 or 72.53% of the study subjects were residential houses that were included in the category of unhealthy houses.